Sob o domínio da metáfora: transposição de imagens poéticas (em) entre Edgar Allan Poe e René Magritte - Moraes, Walmira Sodré Austríaco [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
O corpus desta pesquisa constitui-se dos contos de Edgar Allan Poe, The Domain of Arnheim or Landscape Garden, publicado pela primeira vez em 1847, e Landor’s Cottage. A pendant to “The Domain of Arnheim”, publicado pela primeira vez em 1849. Aos dois contos agrupam-se as pinturas de René Magritte que recebem o mesmo título do conto de Poe: The Domain of Arnheim (1938), The Domain of Arnheim (1944), The Domain of Arnheim (1949) e The Domain of Arnheim (1962). O recorte materializa-se mediante a análise dos efeitos estéticos e das várias produções de sentidos metafóricos registrados nas telas e nos contos. Para tanto, propomos uma discussão que tem como referencial um processo de interpretação sígnica atravessado por uma historicização da relação original entre Poe e Magritte por meio da análise de outras telas e textos subjacentes àqueles que constituem o objeto da nossa investigação. O estudo constrói uma teia de relações em cuja base está a metáfora – pensada em sua historicidade dinâmica – considerada como princípio, meio e fim das injunções estabelecidas. Estimamos, como prioridade, o deslocamento histórico-estético que essa figura sofreu, e a contextualização destaca, portanto, a sua ação transformadora pela qual literatura e pintura interagem por semelhança, por similitude e/ou por dessemelhança. Nesse sentido, a relação dialética proposta constitui-se, no âmbito de nossas discussões, pelo predomínio da metáfora a partir de suas atuações no discurso literário e pictórico e entre eles, e, ainda, em face dos seus deslocamentos. Essa relação privilegia a formação de um quadro teórico que alinhe o ut pictura poesis aos efeitos advindos do uso da metáfora, o que possibilita, a nosso ver, a aproximação efetiva entre literatura (Poe) e pintura (Magritte), com ênfase, sobretudo, nas relações de similaridades estruturais que mantêm entre si.

The corpus of this dissertation is the short stories by Edgar Allan Poe, The Domain of Arnheim or The Landscape Garden, first published in 1847, and Landor’s Cottage. A pendant to “The Domain of Arnheim” first published in 1849. To both tales are the paintings by René Magritte that receive the same title of Poe's short stories: The Domain of Arnheim (1938), The Domain of Arnheim (1944), The Domain of Arnheim (1949) and The Domain of Arnheim (1962). The focus of the research is the analysis of the aesthetic effects and of the various productions of metaphorical meanings registered on the canvas by René Magritte and the short stories by Edgar Allan Poe. In order to accomplish this objective, this dissertation develops a discussion that has as a reference the process of meaning interpretations permeated by a historicization of the original relationship between the two artists through the analysis of other paintings and texts underlying those that, effectively, are the object of the present research. The analysis established with relationships whose base is the metaphor - thought in its dynamic historicity - considered as beginning, middle and end of the established relationships. The study focuses, in the first place, the historical-aesthetic displacement that the metaphor has gone through and this contextualization emphasizes, therefore, the transforming action of this figure of speech through which literature and painting interact between themselves by similarity and/or dissimilarity. In this sense, the dialectical relationship proposed constituted by the predominance of the metaphor from its performances in the literary and pictorial discourse and between themselves and, above all, in their movements. This relationship favors the formation of a theoretical framework that aligns the ut pictura poesis of the effects arisen out of the use of the metaphor, which enables a more effective link between literature (Poe) and painting (Magritte) with emphasis, especially, on the relationship among their structural similarities.

El corpus de esta investigación es los cuentos de Edgar Allan Poe, The Domain of Arnheim or The Landscape Garden, publicada por primera vez en 1847, y Landor’s Cottage. A pendant to “The Domain of Arnheim”, publicada por primera vez en 1849. Los dos cuentos se agrupan las pinturas de René Magritte que reciben el mismo título del cuento de Poe: The Domain of Arnheim (1938), The Domain of Arnheim (1944), The Domain of Arnheim (1949) y The Domain of Arnheim (1962). La delimitación se materializa a través del análisis de efectos estéticos y de las diversas producciones de significados metafóricos inscritos en las pantallas de René Magritte y los cuentos de Edgar Allan Poe. Para este, el trabajo se presenta un debate que tiene como referencia proceso de interpretación medio atravesado por un historicismo la relación original entre los dos artistas mediante el análisis de textos y otras pantallas que aquellos que, efectivamente, son el objeto de esta investigación. El análisis se basa una red de relaciones en que la base es una metáfora, pensaba en su historicidad, considerado como principio, medio y fin de las relaciones establecidas. Según las estimaciones del estudio, como una prioridad, el desplazamiento historia y estética que la metáfora ha sufrido y esta contextualización se destaca, por lo tanto, a la acción transformadora de esta figura por que la literatura y la pintura interactuar por similitud o disimilitud. En este sentido, la relación dialéctica propuesta se lleva a cabo por un predominio de la metáfora de sus actuaciones en los discursos literarios, pictóricos y entre ellos y, sobre todo, en sus desplazamientos Esta relación favorece la formación de un marco teórico que pueda alinear el ut pictura poesis de los efectos derivados de la utilización de la metáfora, lo que hace que el enfoque más eficaz entre la literatura (Poe) y la pintura (Magritte) con énfasis, especialmente en las relaciones de similitud estructural que mantiene entre ellos.
Under the domain of the metaphor: transposition of poetic images (in) between Edgar Allan Poe and René Magritte
Bajo el imperio de la metáfora: incorporación de imágenes poéticas (en) entre Edgar Allan Poe y René Magritte
Keywords: Metáfora; Literatura e pintura; Edgar Allan Poe; René Magritte; Metaphor; Painting and literature; Edgar Allan Poe; René Magritte; Metáfora; Pintura, literatura; Edgar Allan Poe; René Magritte